Biomolecular identification of ancient Mycobacterium tuberculosis complex DNA in human remains from Britain and continental Europe. Issue 2 (14th November 2013) - Müller, Romy; Roberts, Charlotte A.; Brown, Terence A.
ABSTRACT Tuberculosis is known to have afflicted humans throughout history and re‐emerged towards the end of the 20th century, to an extent that it was declared a global emergency in 1993. The aim of this study was to apply a rigorous analytical regime to the detection of Mycobacterium tuberculosis complex (MTBC) DNA in 77 bone and tooth samples from 70 individuals from Britain and continental Europe, spanning the 1st–19th centuries AD. We performed the work in dedicated ancient DNA facilities designed to prevent all types of modern contamination, we checked the authenticity of all products obtained by the polymerase chain reaction, and we based our conclusions on up to four replicate experiments for each sample, some carried out in an independent laboratory. We identified 12 samples that, according to our strict criteria, gave definite evidence for the presence of MTBC DNA, and another 22 that we classified as "probable" or "possible." None of the definite samples came from vertebrae displaying lesions associated with TB. Instead, eight were from ribs displaying visceral new bone formation, one was a tooth from a skeleton with rib lesions, one was taken from a skeleton with endocranial lesions, one from an individual with lesions to the sacrum and sacroiliac joint and the last was from an individual with no lesions indicative of TB or possible TB. Our results add to information on the past temporal and geographical distribution of TB and affirm the suitability of ribs for studying ancient TB. Am J Phys Anthropol 153:178–189, 2014. © 2013 Wiley Periodicals, Inc.